Symposium 8: E-Portfolios: A Student Perspective - McGowan, Kim (Proceedings of the International Conference on Networked Learning, 2008)
This paper looks at the learner experience of using an eportfolio from the perspective of the part time, non-traditional learner enrolled on the Post Graduate Certificate in Learning and Teaching in Higher Education at the University of Cumbria. The learner, who is also employed at Cumbria as an academic librarian, reflects upon the use of an eportfolio to support a post graduate course. In addition the author has worked to engage with the eportfolio by aligning use to existing work practice. She has logged this experience and discusses the advantages and disadvantages of eportfolio use in educational and professional contexts and considers the implications for learner support in an era when UK universities are widening participation in Higher Education. The paper looks at: the motivation of the specific non-traditional learner to engage with the eportfolio: the value of the learner’s engagement with the eportfolio application: whether other systems would have been as useful, or more useful than the eportfolio application: a potential area for development?; In considering the value of the eportfolio as a tool to support study and existing work practice the author considers ease of use, time and administrative burden in relation to existing systems. The characteristics are viewed from the perspective of a non-traditional learner who left full time education prior to the information revolution. Learners starting university in the UK are already expected to use a range of password controlled electronic resources and applications. Traditional 18 year old undergraduates may come to university at ease inhabiting a personal digital space. However, at least 42% of UK learners are part time and non-traditional. In terms of eportfolio use these learners will be disadvantaged from the outset. The author reports that learning to use the application can be time consuming and that learners can be hampered by unreasonable expectations, by a lack of understanding, confidence and technical skill. Nevertheless the author concludes that these issues can be resolved with judiciously applied support and training and that the eportfolio does have the potential to add value to both academic and professional practice.